BUSINESS MANAGEMENT DEVELOPMENT STRATEGY IN MICRO, SMALL AND MEDIUM ENTERPRISES - Siregar, Budi Alamsyah; Suma, Dewi (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2022)
Domestic MSMEs that are highly competitive, innovative and creative are able to expand the ASEAN Economic Community market. However, there are problems that often hinder the development of MSMEs in Deli Serdang Regency, namely weak institutional and individual factors, for this reason efforts are needed to increase the growth of MSMEs with competitive strategies, especially in facing the AEC. The method used is a literature study using descriptive analysis techniques and qualitative research. The results of this research are Porter's Five Forces model consisting of: threat of new entrants, strength of supplier's bargaining position, strength of buyer's bargaining position, threat of substitute or substitute products, strength of competition or competitors, has not been sufficiently applied to MSMEs in Deli Serdang Regency and is very It is necessary to develop a model with the addition of 2 more indicators that will support MSMEs to be able to survive, compete and excel in facing the ASEAN Economy. Community (AEC), namely: Governance, Innovation Capability and Mastery of Technology, Effective Low Cost Strategy for MSMEs in Deli Serdang Regency. This can be seen from the expected goals for business actors (MSMEs), namely being able to increase profits by reducing costs and setting prices which is in accordance with the average industry and business actors (MSMEs), can increase market share by applying lower prices and still achieve or obtain adequate profits from each sale of products or services because costs have been reduced.